Diversity, prevalence and environmental benefits of street tree in Nakhon Si Thammarat, Thailand - Choothong, S.,; Qin, H. ,; Soonsawad, N. , (International Journal of Agricultural Technology, 2016)
Street trees provide a wide range of ecosystem services to cities including improving environmental quality, and socio-economic benefits. Despite their immense importance, there is a limited number of research in terms of diversity and ecosystem services of street trees in Thailand. This research is subjected to diversity, prevalence and environmental benefits of street trees in the district highway of Nakhon Si Thammarat province, southern Thailand. The systematic sampling inventory was conducted on 38 routes of the highway in early 2015. With about 3,000 trees sampled, they are composed of 83 species in 31 families. The five most abundant species are: Cassis fistula (13.51%); Acacia mangium (13.27%); Senna siamea (11.61%); Tamarindus indica (8.25%); and Lagerstroemia floribunda (8.14%). Using the i-Tree Streets model in calculating tree environmental benefits based on the trees’s size and species, the total monetary value of those environmental benefits provided by these street trees is approximately $12 million per year. On average, the value that the city can save is about $40 per tree per year. The first three species that provided the greatest annual value (in the unit of $ per tree per year) are; Ficus religiosa (110); Tamarindus indica (100), Senna siamea (90); on the other hand, Delonix regia provided the lowest annual value of about $3 per tree. The Department of Highway could improve the city environmental quality and economy by selecting tree species with great environmental benefits as well as increasing tree diversity and abundance by planting or replanting more native species such as Tamarindus indica and Senna siamea on the highway.